Cell lines for the study of Lysosomal Storage Diseases: conservation and identity - Correia, Maria I. (2022)
The use of cell lines has revolutionized research in the area of human genetics. The possibility of allowing, at a low cost and relative ease, practical access to biological material bearing in mind the benefit to the patient/family by obtaining samples with adequate informed consent, is a great asset. The accessibility of cell lines from biobanks allows access to samples with all the ethical and feasibility concerns observed. Cell lines are usually cryopreserved in liquid nitrogen and can be maintained in viable conditions for long periods of time. Cell lines allow studies of the causes of the disease, namely: the establishment of cell models, for a better understanding of the pathophysiology; the study of gene interactions; toxicity assays and drug tests; gene editing studies and other types of research. Using fibroblasts from patients with Lysosomal Storage Diseases (LSDs), it was already possible in this laboratory to revert cells to the stem cell state by creating induced pluripotent stem cells (iPSCs) to serve as a model in future studies. This clearly demonstrates the potential of cell lines for research. As with other cell lines, iPSCs can be cryopreserved which increases their potential for use. In order to guarantee the integrity and viability of cryopreserved cell lines, in laboratories, not exclusively dedicated to cell culture (as would be the case of a biobank), it would be advisable to periodically perform random thawing of samples in order to guarantee the identity of the preserved cells, genetic stability and absence of contaminants. There are several ways to do this however, in this work, we present some of the techniques used based on minimal procedures to ensure the cellular integrity of cryopreserved lines. It would be desirable, even in small laboratories, that procedures like these were adopted in a standardized and routine way, to facilitate the success of the subsequent use of cells in research.